The Influence Of Business Capital And Pricing Strategies On The Business Income Of Karawo Artisans In Kota Utara District - Sofyanti Antu; Tri Handayani Amaliah; Ronald S. Badu (International Journal of Economics, Business and Innovation Research, 2026)
This study aims to analyze the influence of business capital and pricing strategies on the business income of karawo artisans in Kota Utara District. Karawo crafts are a superior product typical of Gorontalo which has high artistic and cultural value, but its development still faces constraints of limited capital and a price strategy that is not optimal. The study used a quantitative approach with a survey method of 30 karawo artisan respondents determined through purposive sampling techniques. Data processing was carried out using multiple linear regression analysis supported by validity, reliability, and classical assumption tests. The findings of the study resulted in a regression equation model, namely Y = 1.214 + 0.367X₁ + 0.412X₂. The partial test proved that business capital had a positive and significant influence on business income, which was evidenced by a t-calculated value of 2.585 greater than the t-table of 2.052. In addition, pricing strategies have also proven to have a positive and significant effect, with a t-count value of 2.964 which surpasses the t-table of 2.052. The simultaneous test showed that both variables simultaneously proved to have a significant effect, which was shown by the F-calculated value of 17.32 greater than the F-table of 3.35. Meanwhile, a determination coefficient of 0.562 shows that 56.2% of the variation in operating income can be explained by business capital and pricing strategies. This study concludes that increasing the income of karawo artisans requires strengthening business capital to increase production capacity and implementing pricing policies based on production costs, cultural values attached to products, and consumer purchasing power. The practical implications of this study emphasize the need for capital support and managerial assistance for karawo artisans for business sustainability and the preservation of local culture.